2003
DOI: 10.1007/s00705-003-0144-3
|View full text |Cite
|
Sign up to set email alerts
|

The complete nucleotide sequence of Subterranean clover mottle virus

Abstract: The complete nucleotide sequence of Subterranean clover mottle virus (SCMoV) genomic RNA has been determined. The SCMoV genome is 4,258 nucleotides in length. It shares most nucleotide and amino acid sequence identity with the genome of Lucerne transient streak virus (LTSV). SCMoV RNA encodes four overlapping open reading frames and has a genome organisation similar to that of Cocksfoot mottle virus (CfMV). ORF1 and ORF4 are predicted to encode single proteins. ORF2 is predicted to encode two proteins that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Several isolates of Subterranean clover mottle virus (SCMoV, genus Sobemovirus ), which caused a disease restricted to southwest Australia, were fully sequenced [28]. The highest divergence between two isolates collected in 1991 and 1996, respectively, was 1.2%.…”
Section: Resultsmentioning
confidence: 99%
“…Several isolates of Subterranean clover mottle virus (SCMoV, genus Sobemovirus ), which caused a disease restricted to southwest Australia, were fully sequenced [28]. The highest divergence between two isolates collected in 1991 and 1996, respectively, was 1.2%.…”
Section: Resultsmentioning
confidence: 99%
“…The most 5′ proximal ORF1 encoding protein P1 is situated in weak context for optimal translation initiation [ 47 , 48 ] and this enables pre-bound 40S ribosomes to bypass its start codon and to initiate translation from the subsequent ORF. It has been demonstrated that the deletion of the start codon of SCPMV ORF1 increased translation from downstream ORF2a/2ab, whereas mutations making SCPMV ORF1 translation initiation context more favorable reduced the downstream protein expression [ 49 ].…”
Section: Genomic Organizationmentioning
confidence: 99%
“…Earlier multiple AA sequence alignments conducted by Dwyer et al [3] surprisingly demonstrated similarity of N-terminal part of RdRPs of CfMV-like sobemoviruses to unknown ORF3 products of SCPMV-type sobemovirus genomes, including RGMoV, RYMV, and SeMV. Similarly to our sequencing data, recently published corrected sequences of RYMV [8] and SeMV (Genbank No.AY004291) demonstrated excessive nucleotides in ORF2, which have led to wrongly interpreted genome organization in early publications [2].…”
mentioning
confidence: 98%
“…For other sequenced sobemovirus genomes (CfMV, SCMoV, TRoV), a different, CfMV-type polyprotein coding strategy has been found. Instead of large polyprotein genes with nested ORF3 the genomes of these viruses contain two overlapping ORFs, and putative RdRP's are formed as a C-terminal part of polyprotein via -1 ribosomal frameshifting [2][3][4]. The latest sequencing of RYMV [8] and SeMV (Genbank No.…”
mentioning
confidence: 99%
See 1 more Smart Citation